The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15587/1729-4061.2021.235950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of innovative activity of enterprises in the conditions of European integration

Abstract: The processes of globalization and integration pose new challenges to the economy of any country, in particular, the issues of assessing and stimulating the innovative activity of enterprises in the context of constant transformation arise. Therefore, the purpose of this study was to substantiate the methodology for assessing the safety of the country's innovative environment, based on stimulating the innovative activity of enterprises in the context of European integration. The result of the study is the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Economic security of the enterprise is the protection of the enterprise from negative effects of the external and internal environment, the ability to quickly eliminate various threats or adapt to external conditions without negative consequences. In addition, the economic security of the enterprise is the most efficient use of resources that ensure stable operation [1,31].…”
Section: Economic Security Of the Enterprisementioning
confidence: 99%
“…Economic security of the enterprise is the protection of the enterprise from negative effects of the external and internal environment, the ability to quickly eliminate various threats or adapt to external conditions without negative consequences. In addition, the economic security of the enterprise is the most efficient use of resources that ensure stable operation [1,31].…”
Section: Economic Security Of the Enterprisementioning
confidence: 99%
“…Somewhat similar is the structure of the innovative potential defined by A. Dziubina: scientific, production-technological, financial, informational, logistical, personnel, and marketing potentials [3]. Scientists T. Zubko, I. Kovshova, N. Ilchenko, V. Laptieva and I. Vavdiichyk generally share the opinion on that the innovative potential of an enterprise represents the existing latent possibilities of attracting and using resources aimed at adopting, introducing innovations that can be involved to achieve the objectives of economic agents; they also concluded that it consists of marketing, information, logistical, personnel, and financial potentials [31]. The innovative potential of an agricultural enterprise is generally identical, according to S. Syrtseva, to the resource potential, highlighting its land, labor, logistical, financial, and informational components [23].…”
Section: Literature Reviewmentioning
confidence: 99%